Moral-Ethics-Belief Values Towards Indonesian Puppet (Wayang Kulit) Performance Arts - Rumambo Pandin, Moses Glorino (Utopía y Praxis Latinoamericana, 2020)
ABSTRACTThe study aims to discover the values of Wayang Kulit, puppet performance arts in Jogjakarta Indonesia. The study used a qualitative philosophical approach through literature and observational-field study. The results of the study discovered that moral-ethics and traditional belief are the source of central values that puppet show carried out to the spectators. The puppet show was not only attracted people's surroundings but give a chance of worldly pragmatics purpose of people. Values of moral-ethics, faith, and arts are harmoniously united without dominating each other.